Robust Phylogeny of Tetrastigma (Vitaceae) Based on Ten Plastid DNA Regions: Implications for Infrageneric Classification and Seed Character Evolution - Habib, Sadaf; Dang, Viet-Cuong; Ickert-Bond, Stefanie M.; Zhang, Jin-Long; Lu, Li-Min; Wen, Jun; Chen, Zhi-Duan (Frontiers in Plant Science, 2017)
Tetrastigma (Miq.) Planch. is one of the most species-rich genera of the economically and agronomically important grape family Vitaceae. It includes ca. 95 species widely distributed in the tropics and subtropics of Asia and Australia. Species of Tetrastigma exhibit great diversity in both vegetative and reproductive characters. Here we inferred a well-supported phylogeny of Tetrastigma based on ten chloroplast DNA regions with an expanded taxon sampling of 72 species and two varieties. Our molecular results support six major clades within Tetrastigma and the relationships among these clades were well resolved. We also documented seed morphology of 44 species covering the six major clades of the genus. Ancestral states of eight characters (seed shape, seed surface rumination pattern, chalaza length/width ratio, chalaza position, ventral infold position, ventral infold divergence, ventral infold depth in cross section, and endosperm shape) were reconstructed in Mesquite and R with four models. Character optimizations suggest that all character states have evolved multiple times except that the irregular shaped surface rumination has derived only once in Tetrastigma. We evaluated the taxonomic importance of seed morphology and identified potential morphological evidence to support each major clade. Our comprehensive analyses of Tetrastigma shed insights into the infrageneric classification of this morphologically diverse and ecologically important genus in tropical and subtropical Asia.